Preliminary study on the isolation, spectroscopic characterisation and antioxidant property of humic acid (HA) from Santa barbara artesian well-water. - Lloren, Ronald Bernas (2009.)
The water at Puso Montinola, Barangay Montinola in Santa Barbara, Iloilo has a color which ranges from light yellow to deep brown. The coloration is mainly due to humic acids (HA). The humic acids were isolated through DAX-8 resin, acid precipitation (concentrated HCI), and through freeze-and-thaw done for a couple of times. The absorbances of the liquid samples using GENESYS UV-Vis spectrophotometer were read, before and after treatment. A decrease in the absorbance readings of the liquid after each treatment was noticed. The IR spectra of isolated dried HA were analyzed using Thermo Nicolet Avatar 330. the IR spectra of the freeze-and oven-dried samples were almost the same, with only slight differences on the absorbances readings. The extracted HA's potential antioxidant property was likewise investigated using Ferric Ion Reducing Antioxidant Power (FRAP Assay and Folin Ciocalteu Reagent (FCR), an assay test for the Total Phenols present. Reducing capacities increased with increasing volumes (200, 500, 1000 uL) and concentrations (250mg/L, 0.0110 g/mL) of HA. The total phenolic compounds in the extracted HA increased at 250 mg/L (37.363 ug GAE) and 0.0110 g/mL (294.54 ug GAE) compared to that of the neat water sample (29.114 ug GAE).
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Artesian Well-Water -- Santa Barbara, Iloiklo; Antioxidant Property -- Humic Acid (HA) -- Artesian Well-Water.